2018
DOI: 10.12669/pjms.345.15659
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of transcutaneous electrical nerve stimulation in management of neuropathic pain in patients with post traumatic incomplete spinal cord injuries

Abstract: Objective:To determine the effectiveness of Transcutaneous Electrical Nerve Stimulation (TENS) in management of neuropathic pain in post-traumatic incomplete spinal cord injury patients.Methods:A quasi-experimental study was conducted at from January 2017 to June 2017 at Paraplegic Center Hayatabad, Peshawar. Total 60 incomplete spinal cord injured patients with diagnosis of neuropathic pain were subjected to high frequency TENS of 80 HZ. One session was of 45 minutes while there were two sessions per day. TEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…These results also indicate that TENS induces substantial effects in patients with SCI. A total of 33 patients with SCI were enrolled and were randomly assigned to the TENS and control groups ( 222 ). Patients in the TENS groups received 30 min of TENS, while those in the control group were assigned 30 min of sham TENS, once a day for 10 days.…”
Section: Non-pharmacological Therapies For Sci ( Fig 3 mentioning
confidence: 99%
“…These results also indicate that TENS induces substantial effects in patients with SCI. A total of 33 patients with SCI were enrolled and were randomly assigned to the TENS and control groups ( 222 ). Patients in the TENS groups received 30 min of TENS, while those in the control group were assigned 30 min of sham TENS, once a day for 10 days.…”
Section: Non-pharmacological Therapies For Sci ( Fig 3 mentioning
confidence: 99%
“…Previous studies have reported that cervical SCI are less common as compared to thoracic and lumbar injuries, 15,16 however exact statistics about cervical tetraplegic SCI patients in Pakistan are not available. Literature search also revealed that there is limited literature available regarding rehabilitation outcomes in SCI patients in Pakistani settings 2,17 while there was no published research study which reported OT outcomes in SCI patients in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results are also reported by other studies conducted in Pakistan. [14][15][16][17] Burns were common among participants at initial presentation. Electricity related injuries are almost always associated with burns.…”
Section: Discussionmentioning
confidence: 99%